Peran Masyarakat Dalam Mencegah Dan Menanggulangi Bullying - Sa'diyah, Nur Khalimatus; Enggarsasi, Umi (Universitas Wijaya Kusuma Surabaya, 2025)
Community Service in the form of legal counseling on the Role of the Community in Preventing and Handling Bullying aims to increase public legal awareness regarding the dangers of bullying and the steps that can be taken to prevent and handle it. Bullying, whether in the form of physical, verbal, or cyberbullying, has serious impacts on victims, including psychological and social disorders. From a legal perspective, bullying can be categorized as an act that violates human rights and can be subject to sanctions based on applicable laws and regulations, such as the Child Protection Law, the Criminal Code, and the ITE Law. Therefore, the community has an important role in creating a safe environment, including through education, prevention, and reporting to the authorities if a bullying case occurs. This counseling method uses Empirical Jurisprudence, participants are given an understanding of the forms of bullying, its legal impacts, and the role of the Community, family, school, and community in preventing and handling bullying cases. The community is expected not only to be a spectator, but also to play an active role in building an anti-bullying culture by providing support to victims, reporting perpetrators, and educating children and adolescents about the importance of mutual respect. With the active role of the community, it is hoped that the number of bullying cases can be reduced and a safer and more equitable environment can be created for all individuals.